Comparative Efficacy of Plant Extracts and Probiotics on Growth and Gut Health in Chickens with Necrotic Enteritis - Ruiting Zhang; Jia Yang; Qingjie Wang; Dandan Hu; Qiping Zhao; Shunhai Zhu; Yu Qiao; Fanghe Zhao; Zhongchuang Wang; Jinwen Wang; Yu Yu; Hongyu Han; et al. (Animals)
Necrotic enteritis (NE), caused by Clostridium perfringens, represents a major economic challenge to poultry production. This study evaluated the effects of four plant extracts—Astragalus, pomegranate peel, Sophora flavescens, and Artemisia annua—in combination with B. subtilis, as potential antibiotic alternatives for controlling NE. Using an experimentally induced NE model produced by coinfection with Eimeria maxima and C. perfringens, 288 chickens were divided into 12 groups to assess growth performance, intestinal lesions, and inflammatory markers. Compared with the enramycin group, the pomegranate peel extract group had a 9.9% increase in body weight gain (BWG), significant enhancement in claudin-2 expression, and reduced production of inflammatory factors. Compared with the infected control group, the combination of A. annua extract and B. subtilis resulted in the lowest intestinal lesion scores. The claudin-2, occludin, and zonula occludens-1 expression levels in the group treated with S. flavescens extract combined with B. subtilis increased to the highest levels compared to those in the healthy control group. These findings emphasize the potential of plant extracts, particularly pomegranate peel and A. annua with B. subtilis, as natural alternatives for NE management in poultry, providing a promising approach to reducing reliance on antibiotics.